The level of Emotional Value and Customer Trust Assessment of State-Owned Enterprise Bank Customer of Kebayoran Baru South Jakarta - Rusdian, Budi; Yunus, Riza Mahmud (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2024)
Purpose: The rapid development of economy in Indonesia has given a positive influence to the services sectors including State-Owned Enterprise banking, everyone will need banks as their business partners. Customers’ trust is a great asset for banks. The long-term relationship of customer-banks depends on the presence of customers’ trust on the banks. The significance of this phenomenon in banking industry becomes more critical where banks have to know their individual customers as well as contextual factors that influence on customers’ emotional value and customers trust.Design/methodology: This study aims to measure the level of customers emotional value and customers’ trust. 400 customers from any state-owned enterprise bank in Kebayoran Baru - South Jakarta were selected to form the sampling frame.Findings: The results show that both emotional value and customer trust is at a good level. All products, services and product features are able to create the emotional value expected by customers. All employees, products and facilities provided by bank are able to create consumers trust in the bank.Practical implications: The empirical implication of this research is to determine the conditions and the level of emotional value and customer trust in state-owned enterprise bank.Originality/Value: All companies in the banking industry must increase their awareness of the importance of providing value related to the emotional side of customers and also the importance of maintaining customer trust. The contribution of this research focuses on efforts to attract customer through their emotional value and trust.Keywors: Emotional Value, Customer Trust, State-Owned Enterprise Bank.